Single‐shot full strain tensor determination with microbeam X‐ray Laue diffraction and a two‐dimensional energy‐dispersive detector. Issue 3 (30th May 2017) - Abboud, A.; Kirchlechner, C.; Keckes, J.; Conka Nurdan, T.; Send, S.; Micha, J. S.; Ulrich, O.; Hartmann, R.; Strüder, L.; Pietsch, U.
Abstract : By simultaneously measuring changes in energy and reflection angle of Laue spots with respect to a reference position, it is possible to measure all lattice parameters of a unit cell and calculate the full strain/stress tensors in a single‐shot experiment with high spatial resolution. Abstract : The full strain and stress tensor determination in a triaxially stressed single crystal using X‐ray diffraction requires a series of lattice spacing measurements at different crystal orientations. This can be achieved using a tunable X‐ray source. This article reports on a novel experimental procedure for single‐shot full strain tensor determination using polychromatic synchrotron radiation with an energy range from 5 to 23 keV. Microbeam X‐ray Laue diffraction patterns were collected from a copper micro‐bending beam along the central axis (centroid of the cross section). Taking advantage of a two‐dimensional energy‐dispersive X‐ray detector (pnCCD), the position and energy of the collected Laue spots were measured for multiple positions on the sample, allowing the measurement of variations in the local microstructure. At the same time, both the deviatoric and hydrostatic components of the elastic strain and stress tensors were calculated.